Enhanced antibody responses in CD19-Cre mice - Cunha, Diogo M.; Hernández-Pérez, Sara; Mattila, Pieta K. (Springer Nature, 2025)
CD19-Cre is an important and widely used Cre-lox model for B cell-specific genetic manipulation in murine systems. Mice carrying one allele of CD19-Cre are, at the same time, rendered heterozygote for CD19, a crucial coreceptor of the B cell antigen receptor (BCR). As a result, CD19-Cre mice exhibit diminished expression levels of CD19, with potential, yet insufficiently examined, consequences in B cell activation. Here, we report significantly heightened antibody responses upon both T-dependent (NP-KLH) and T-independent (NP-Ficoll) immunizations as well as elevated levels of basal IgM immunoglobulin levels in CD19-Cre mice. In vitro, we observed enhanced class-switch recombination and a moderate reduction in B cell proliferation upon LPS and IFNγ stimulation, yet no drastic differences in BCR signalling. Our findings warrant careful consideration in the use of CD19-Cre mouse model in B cell research.